SELF-IDENTIFICATION OF CHILDREN WITH HEARING IMPAIRMENT - Datsenko, Darya (Educological discourse, 2022)
This article examines the process of formation of self-identification of children with hearing impairment. In particular, the main attention is focused on the formation of self-identification of a hearing-impaired child, as a result of reading artistic works. The paper outlines the general state of the inclusive educational and teaching process and suggests ways of solving personal barriers through the implementation of quality literary teaching in the educational and teaching process